Entrepreneurship Education as a Key Mediator in the Path from Motivation and Knowledge to Entrepreneurial Interest - Andika Isma; Soussou Raharimalala (Pinisi Journal of Entrepreneurship Review, 2024)
This study investigates the impact of motivation and knowledge on entrepreneurial interest among students at Universitas Negeri Makassar, with a focus on entrepreneurship education as a mediating factor. The research adopts a quantitative approach, utilizing a survey method to gather data. The study examines how individual motivation—whether driven by personal passion, career aspirations, or a desire to create change—can significantly influence the development of entrepreneurial interest. Additionally, entrepreneurship education is highlighted as a crucial element that provides the necessary knowledge and practical skills to enhance this motivation. The findings indicate that motivation and knowledge play pivotal roles in shaping entrepreneurial interest, particularly when reinforced by a strong educational foundation. Entrepreneurship education equips students with the tools to understand the various aspects of entrepreneurship, identify opportunities, and navigate business challenges. The synergy between high motivation and comprehensive entrepreneurial knowledge fosters a conducive environment for cultivating entrepreneurial interest, ultimately preparing students to pursue and succeed in entrepreneurial endeavors.